1968
DOI: 10.1203/00006450-196803000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Low Birth Weight. Psychological Status at Eight to Ten Years of Age

Abstract: ExtractFive hundred low birth weight children and 492 full-term infants were seen when approximately 40 weeks of age for a pediatric-neurologic examination. Of these, 822 provided the data upon which this report is based. To each child, when eight to ten years of age, there was administered ten subtests of the Wechsler Intelligence Test for Children (WISG), the Bender Gestalt Test and the Wide Range Reading and Spelling Achievement Test. In addition, observations were recorded regarding speech articulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0
2

Year Published

1970
1970
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 5 publications
6
43
0
2
Order By: Relevance
“…At ages six through seven, IQ scores on the Stanford-Binet test were obtained and at ages eight to nine, WISC IQs are available. At both age levels, lower birth weights were associated with lower IQs (Wiener, et al 1965(Wiener, et al , 1968.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…At ages six through seven, IQ scores on the Stanford-Binet test were obtained and at ages eight to nine, WISC IQs are available. At both age levels, lower birth weights were associated with lower IQs (Wiener, et al 1965(Wiener, et al , 1968.…”
Section: Introductionmentioning
confidence: 93%
“…They therefore, in association with Rider and Harper (1956) undertook a prospective study of a balanced sample of 500 premature infants born in Baltimore in 1952 and compared them with full-term control infants born in the same hospitals who were matched with the prematures for race, maternal age, parity, season of birth and socioeconomic status. Four hundred pairs of cases and controls were still available for study when the children were between six and seven years of age, and examination of the sample indicated that at this age the prematures and fullterm children continued to be matched for maternal and social attributes (Wiener, et al 1965). Findings at various ages persistently showed the prematures to be less intellectually competent than the controls.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term neurodevelopmental, behavioral, cognitive, and motor sequelae of prematurity have been documented extensively, [1][2][3][4][5][6][7][8] including reports that predate the increase in survival of extremely small and sick infants. [9][10][11][12] In addition to children with frank neurologic and sensory impairment, a spectrum of neurodevelopmental and behavioral disorders are more prevalent in formerly premature infants than in their peers throughout infancy and childhood. Sequelae in children followed to school age include deficits in cognition and problems with learning, motor coordination, behavior, and attention.…”
mentioning
confidence: 99%
“…In fact, many studies are available to show that babies "born too soon or born too small" (46) are at a high risk for developing behavioral disorders, particularly hyperactivity and learning disabilities (41)(42)(43)(44)(45)(105)(106)(107)(108)(109), with boys displaying this syndrome more often than girls (46). Since only a small proportion of the high-risk children are diagnosed as suffering from behavioral abnormalities, and some of the potential disorders may be prevented by special care, it may be advisable to screen those at risk for the presence of retarded brain development and its extent by using the magnetic resonance imaging technique.…”
Section: Morphological and Behavioral Markers Of Retarded Brain Develmentioning
confidence: 99%
“…In a retrospective study, Pasamanick and Knobloch (36) found that a higher proportion of children with school problems than matched control children had perinatal medical complications, and that their major symptom was hyperactivity. Several large-scale recent studies have established that prematurely born babies and small-for-date babies are at a high risk for developing hyperactivity and/or learning disabilities (41)(42)(43)(44)(45)(46).…”
mentioning
confidence: 99%